Penciptaan Desain Kebaya Bergaya Funky Bertema “Kebaya Around The World“ dengan Inspirasi Bar Jacket - Kuncoro, Argi Dwi; Arifiana, Deny (BAJU: Journal of Fashion and Textile Design Unesa, 2024)
The aim of this research is, among other things, to describe the process and results of creating a funky style kebaya design with the theme "kebaya around the world" with the inspiration of a bar jacket. The theme “Kebaya Around the World” was chosen to align the creative process in processing the essence of tradition in kebaya and modern funky style. Research includes creation research, which uses the Practice-Ied Research method, which consists of 4 stages which include (1) exploration, (2) design process, (3) embodiment of the work, and (4) dissemination of the work. The results of this research show that the process of creation Funky kebaya design with an around the world kebaya theme, inspired by the bar jacket style includes exploring the source of ideas, creating alternative designs, realizing the work and disseminating the work in the form of presentation via mannequin displays and demonstrated by model in accordance with the theory of practice-led research in the form of 1 set design and produce ready-to-wear clothing in the form of kebaya, trousers and accessories with funky style, and the theme of kebaya around the world.